Interfacial Reactions of Tetraphenylporphyrin with Cobalt-Oxide Thin Films - Wechsler, Daniel; Fernandez, Cynthia C.; Tariq, Quratulain; Tsud, Nataliya; Prince, Kevin C.; Williams, Federico Jose; Steinrück, Hans-Peter; Lytken, Ole (Chemistry - A European Journal, 2019)
We have studied the adsorption and interfacial reactions of 2H-tetraphenylporphyrin (2HTPP) with cobalt-terminated Co3O4(111) and oxygen-terminated CoO(111) thin films using synchrotron-radiation X-ray photoelectron spectroscopy. Already at 275 K, we find evidence for the formation of a metalated species, most likely CoTPP, on both surfaces. The degree of self-metalation increases with temperature on both surfaces until 475 K, where the metalation is almost complete. At 575 K the porphyrin coverage decreases drastically on the reducible cobalt-terminated Co3O4(111) surface, while higher temperatures are needed on the non-reducible oxygen-terminated CoO(111). The low temperature self-metalation is similar to that observed on MgO(100) surfaces, but drastically different from that observed on TiO2(110), where no self-metalation is observed at room temperature.
CRIS-Team WoS Importer:2019-10-04